2009
DOI: 10.1158/1535-7163.mct-08-1061
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of vascular endothelial growth factor–mediated angiogenesis in tamoxifen-resistant breast cancer cells: role of Pin1 overexpression

Abstract: Acquired resistance to tamoxifen (TAM) is a serious therapeutic problem in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 48 publications
4
39
0
Order By: Relevance
“…We showed that the Pin1 protein level was consistently increased in TAMR-MCF-7 cells compared to control MCF-7 cells (Kim et al, 2009a;2009b) (Fig. 1A).…”
Section: Transcriptional Activation Of the Pin1 Gene In Tamr-mcf-7 Cellsmentioning
confidence: 84%
See 4 more Smart Citations
“…We showed that the Pin1 protein level was consistently increased in TAMR-MCF-7 cells compared to control MCF-7 cells (Kim et al, 2009a;2009b) (Fig. 1A).…”
Section: Transcriptional Activation Of the Pin1 Gene In Tamr-mcf-7 Cellsmentioning
confidence: 84%
“…Unfortunately, resistance to hormonal therapy is a major clinical problem -most cancer cells can utilize alternative mechanisms for growth and survival after initiation of first-line endocrine therapy (Ali et al, 2002). A series of our studies revealed that both VEGF-mediated angiogenesis and snail-dependent epithelial mesenchymal transitions were stimulated in TAMresistant breast cancer cells, and Pin1 overexpression in this cell type is a critical event for both processes (Kim et al, 2008;2009a;2009b). In the present study, we demonstrated that Pin1 overexpression in TAMR-MCF-7 cells was dependent on transcriptional activation of the Pin1 gene.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations